A Far‐Red Emitting Fluorescent Chemogenetic Reporter for In Vivo Molecular Imaging. Issue 41 (18th August 2020) - Li, Chenge; Tebo, Alison G.; Thauvin, Marion; Plamont, Marie‐Aude; Volovitch, Michel; Morin, Xavier; Vriz, Sophie; Gautier, Arnaud
Abstract: Far‐red emitting fluorescent labels are highly desirable for spectral multiplexing and deep tissue imaging. Here, we describe the generation of frFAST (far‐red Fluorescence Activating and absorption Shifting Tag), a 14‐kDa monomeric protein that forms a bright far‐red fluorescent assembly with (4‐hydroxy‐3‐methoxy‐phenyl)allylidene rhodanine (HPAR‐3OM). As HPAR‐3OM is essentially non‐fluorescent in solution and in cells, frFAST can be imaged with high contrast in presence of free HPAR‐3OM, which allowed the rapid and efficient imaging of frFAST fusions in live cells, zebrafish embryo/larvae, and chicken embryos. Beyond enabling the genetic encoding of far‐red fluorescence, frFAST allowed the design of a far‐red chemogenetic reporter of protein–protein interactions, demonstrating its great potential for the design of innovative far‐red emitting biosensors. Abstract : Far‐red emitting fluorescent labels are highly desirable for spectral multiplexing and deep tissue imaging. Here, we report a far‐red fluorescent chemogenetic reporter for the on‐demand imaging of fusion proteins in cells and in living multicellular organisms.